Peranan Transportasi Publik dalam Pengurangan Kemacetan di Jakarta - Aryanto Nur; Yorrell Jensen Isak; Mochammad Eric Adyatma; Rifaldi Ryandhika; Muhammad Rafly Ajiansyah (Journal Of Informatics And Busisnes, 2024)
Traffic congestion in Jakarta has become a complex and ongoing problem, affecting people's quality of life and the efficiency of the transport system. This abstract discusses the causes, impacts, and solutions of congestion in Indonesia's capital city. Congestion in Jakarta is caused by various factors, including rapid population growth, an increasing number of private vehicles, and inadequate transport infrastructure. Data shows that the number of motor vehicles in Jakarta has reached 26.4 million units, while the length of roads is only 6,653 kilometres. This creates an imbalance between road capacity and traffic volume, causing a significant build-up of vehicles. The average travel time for a 10-kilometre distance during peak hours can reach 32 minutes, much longer than international standards. The impacts of congestion include increased travel time, stress for motorists, and economic losses due to reduced productivity. In addition, congestion also impacts environmental quality by increasing vehicle exhaust emissions. The government's efforts to address this issue through transport infrastructure development have not been fully effective in reducing congestion. This requires improved public transport, better traffic management, and public awareness of the importance of using public transport. Addressing congestion in Jakarta requires cooperation between the government, the community and other parties to create a sustainable solution.